The Microcephaly-Associated Protein Wdr62/CG7337 Is Required to Maintain Centrosome Asymmetry in Drosophila Neuroblasts. - Ramdas Nair, A.; Singh, P.; Salvador Garcia, D.; Rodriguez-Crespo, D.; Egger, B.; Cabernard, C. (Cell reports, 2016)
Centrosome asymmetry has been implicated in stem cell fate maintenance in both flies and vertebrates, but the underlying molecular mechanisms are incompletely understood. Here, we report that loss of CG7337, the fly ortholog of WDR62, compromises interphase centrosome asymmetry in fly neural stem cells (neuroblasts). Wdr62 maintains an active interphase microtubule-organizing center (MTOC) by stabilizing microtubules (MTs), which are necessary for sustained recruitment of Polo/Plk1 to the pericentriolar matrix (PCM) and downregulation of Pericentrin-like protein (Plp). The loss of an active MTOC in wdr62 mutants compromises centrosome positioning, spindle orientation, and biased centrosome segregation. wdr62 mutant flies also have an ?40% reduction in brain size as a result of cell-cycle delays. We propose that CG7337/Wdr62, a microtubule-associated protein, is required for the maintenance of interphase microtubules, thereby regulating centrosomal Polo and Plp levels. Independent of this function, Wdr62 is also required for the timely mitotic entry of neural stem cells.